CRISIS IN THE EURO AREA: COOPETITIVE GAME SOLUTIONS AS NEW POLICY TOOLS - CARFÌ, David; SCHILIRÒ, Daniele (Theoretical and Practical Research in Economic Fields, 2011)
The crisis within the euro area has become frequent during 2010. First was the Greek economy to face a default problem of its sovreign debt, in November it was Ireland who has been in a serious financial situation at the verge of collapse causing difficulties to the euro. In this contribution we focus on the Greek crisis and we suggest, through a model of competition based on game theory and conceived at a macro level, feasible solutions in a cooperative perspective for the divergent interests which drive the economic policies in Germany and Greece, with the aim of improving the position of Greece, Germany and the whole euro area, also making a contribution to expand the set of macroeconomic policy tools. By means of our general analytical framework of competition, we show the strategies that could bring to feasible solutions in a cooperative perspective for Germany and Greece, where these feasible solutions aim at offering a win-win outcome for both countries, letting them to share the pie fairly within a growth path represented by a non-zero sum game. A remarkable analytical result of our work consists in the determination of the win-win solution by a new selection method on the transferable utility Pareto boundary of the competitive game.